Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1002/pon.2960010305
|View full text |Cite
|
Sign up to set email alerts
|

Do psychosocial factors influence the course of breast cancer? A review of recent literature, methodological problems and future directions

Abstract: The course of breast cancer is highly variable, and only part of the variability in progression rate can be predicted by clinicopathological factors. It is suggested that some of the variation may be ascribed to behavioral factors, but their importance in determining progression of breast cancer is still controversial. Several groups have found an association between progression of breast cancer and psychosocial factors including stressful life events, the expression of negative emotions-anger and anxiety-the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…It can serve not only to distinguish patients with a longer expected survival rate from those who might be facing a sooner death but also to estimate the patient's survival time. Subjective measurements of how patients facing a fatal outcome from brain neoplasm feel, how they deal with life and the disease and their psychosocial state as a whole, obviously carry a greater potential for prolonged life than standard somatic factors [23]. It is essential that our findings are applied to a larger sample of patients to go beyond the natural limitations of a pilot study and that other investigators also elucidate the question whether successful attempts to improve quality of life can promote prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
“…It can serve not only to distinguish patients with a longer expected survival rate from those who might be facing a sooner death but also to estimate the patient's survival time. Subjective measurements of how patients facing a fatal outcome from brain neoplasm feel, how they deal with life and the disease and their psychosocial state as a whole, obviously carry a greater potential for prolonged life than standard somatic factors [23]. It is essential that our findings are applied to a larger sample of patients to go beyond the natural limitations of a pilot study and that other investigators also elucidate the question whether successful attempts to improve quality of life can promote prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful experiences, depression and particular personality characteristics (type C behaviour) have been advanced as possible psychological precursors of cancer. Stress: The majority of controlled studies have failed to confirm an association between the occurrence of stressful events-including loss of a loved person-and the onset of cancer (Muslin et al, 1966; Greer and Morris, 1975; Schonfield, 1975;Priestman et al, 1985;Ewertz, 1986), but some recent studies reported significant associations between diagnosis of breast cancer and adverse life events in the preceding 6 to 8 years (Forsen, 1991;Geyer, 1991) and the diagnosis of colorectal cancer and such events in the preceding 5 years (Kune et al, 1991). Studies of the influence of stress are greatly hampered by our ignorance of the time of onset of the disease which may occur many years before the clinical appearance of cancer.…”
Section: Psychological Contribution To the Development And Course Of mentioning
confidence: 99%
“…For example, inadequate sample size and the omission of important prognostic indicators have been commonly cited as problematic (Mulder et al, 1992). Research in this area is also confused by the diverse array of study designs with differences in the psychosocial constructs measured, cancer types sampled, prognostic covariates included, type of analysis and timing of assessments.…”
mentioning
confidence: 99%